ECTHR_COMMITTEE 62547/09 vom 21. Juli 2016 , AFFAIRE VOÏVODA ET AUTRES c. GRÈCE - Ecthr Committee (2016)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Délai raisonnable); Violation: 6;6-1